HISTORIOGRAPHY OF THE STUDY OF STATE PRACTICES AND THE JUDICIARY OF SOUTHERN UKRAINIAN TERRITORIES: GENERAL CHARACTERISTICS - Oleg Vuyiv; Maryna Bulkat (Публічне управління та регіональний розвиток)
For a long time, domestic historians of law and the state and other branch scientists, who were engaged in the study of the southern territories, were focused on the practices of the imperial period, and later – of the period of Soviet occupation. However, the approach to the analysis of the processes of development of the southern Ukrainian territories in the core branches of historical science has now been radically changed and deepened. Methodological approaches to conducting research in related scientific fields also need rethinking. The methodological basis of scientific research is the results of historiographical analysis, a step-by-step understanding of the achievements of each historical period. The object of the history of Ukrainian statehood, and therefore of historical and legal studies of this topic, given in the 9th–10th centuries. and geographically delineated by the north and west of modern Ukraine. On the other hand, the sources about the experience of statesmanship and the Ukrainian colonization of the southern territories are relatively limited and have important features. From the beginning of the annals, domestic authors adhered to pro-Ukrainian rhetoric in matters of the formation of the Kyiv state and its interaction with the Khazar Khaganate, which controlled the southern Ukrainian lands at that time, with the polities of the Pechenegs, Polovtsians, and other steppe peoples who lived there. For an objective analysis of the experience of state practices in southern Ukrainian territories and their impact on the formation of Ukrainian culture and the state, priority should be given to documentary sources and specific archaeological data. Not a small role in this context is currently assigned to the study of oriental sources, taking into account the historiographic achievements of the scientific field of oriental studies. It is important to rethink the position of domestic scientists who pointed to the close connection between the state practices of the Kyiv State and the Steppe, the influence of the steppe culture on the formation of Ukrainian culture and statehood. The analysis of the processes that took place during the period when the Ukrainian and Polovtsian troops were defeated by the Mongols was marked by similar historiographic features. Domestic sources and folklore of this period are full of traumatic experiences. Therefore, for a comprehensive analysis, one should take into account eastern sources, in particular chronicles, and historiographical monuments of other European states. This approach will serve to objectify the experience of the southern Ukrainian terrain. During the period of statelessness, the statist practices of the Lithuanian and Lithuanian-Polish states on the one hand and the Crimean Khanate and the Ottoman Empire on the other were widespread in the southern Ukrainian lands. Important historiographic sources for a comprehensive understanding of the experience of the southern territories in this period, as well as taking into account the modern vector on the pan-European context of Ukrainian history, are taking into account the provisions proposed by Lithuanian and Polish scientists, the Polish-Lithuanian historiography of Ukraine, documents of the Crimean Khanate, archives of the Ottoman Empire etc. In the course of conducting historical and legal studies of the southern territories, one cannot ignore the numerous domestic sources of the period of the Ukrainian Cossack Hetmanate state, their content and significance for national state-building should be thoroughly reconsidered. Such a methodological approach to the expansion of historiographical horizons is predicted to contribute to the renewal of the subject of historical-legal and other branch studies, which until now has been focused on the study of state practices and judicial bodies of the imperial period, and later – the period of Soviet occupation; popularization of objective scientific knowledge about the history of the Ukrainian law, state and judiciary; the role of the experience of southern Ukrainian territories in their formation.